MyoD Is a Novel Activator of Porcine FIT1 Gene by Interacting with the Canonical E-Box Element during Myogenesis - Yan, Chi (Int J Mol Sci, 2015)
Fat-induced transcript 1 (FIT1/FITM1) gene is a member of the conserved gene family important for triglyceride-rich lipid droplet accumulation. FIT1 gene displays a similar muscle-specific expression across pigs, mice, and humans. Thus pigs can act as a useful model of many human diseases resulting from misexpression of FIT1 gene. Triglyceride content in skeletal muscle plays a key role in pork meat quality and flavors. An insertion/deletion mutation in porcine FIT1 coding region shows a high correlation with a series of fat traits. To gain better knowledge of the potential role of FIT1 gene in human diseases and the correlations with pork meat quality, our attention is given to the region upstream of the porcine FIT1 coding sequence. We cloned ~1 kb of the 5′-flanking region of porcine FIT1 gene to define the role of this sequence in modulating the myogenic expression. A canonical E-box element that activated porcine FIT1 promoter activity during myogenesis was identified. Further analysis demonstrated that promoter activity was induced by overexpression of MyoD1, which bound to this canonical E-box during C2C12 differentiation. This is the first evidence that FIT1 as the direct novel target of MyoD is involved in muscle development.